2020
DOI: 10.1016/j.msard.2020.102195
|View full text |Cite
|
Sign up to set email alerts
|

B-cell depleting therapies may affect susceptibility to acute respiratory illness among patients with multiple sclerosis during the early COVID-19 epidemic in Iran

Abstract: To determine whether the course of COVID-19 is more severe in patients with MS and if MS diseasemodifying treatments (DMTs) affect the risk of contracting the disease. Methods: In a cross-sectional survey, data were collected by sending a questionnaire to 2000 patients with a demyelinating disease through an online portal system. Collected data included the current MS DMT and patientreported disability level, history of recent sick contact, recent fever, respiratory symptoms, diagnosis with COVID-19, and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
168
2
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(190 citation statements)
references
References 21 publications
14
168
2
6
Order By: Relevance
“…However, in another study in Iran, 712 patients with MS filled out a questionnaire about COVID-19 symptoms, of which 34 patients (4.8%) had COVID-19 symptoms. It was indicated that the use of B-cell depletion drugs can increase the risk of COVID-19 (Safavi et al, 2020), which is consistent with our findings. Increase in the risk of COVID-19 through B-cell depleting therapies was expected.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in another study in Iran, 712 patients with MS filled out a questionnaire about COVID-19 symptoms, of which 34 patients (4.8%) had COVID-19 symptoms. It was indicated that the use of B-cell depletion drugs can increase the risk of COVID-19 (Safavi et al, 2020), which is consistent with our findings. Increase in the risk of COVID-19 through B-cell depleting therapies was expected.…”
Section: Discussionsupporting
confidence: 92%
“…This study examines the rate of diagnosis of COVID-19 as well as the rate of hospitalization and prognosis in MS patients. In addition, our study assesses these ratios using a larger sample size and different patients from previous report from Iran (Safavi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Their use is associated with IgM deficiency in a substantial number of patients, while their impact on IgG and IgA levels is more limited (Kridin and Ahmed, 2020). In line with our data, recent studies reported that anti-CD20 therapy could be associated with a higher susceptibility to contract SARS-CoV-2 and develop severe COVID-19 (Guilpain et al, 2020;Hughes et al, 2020;Safavi et al, 2020;Schulze-Koops et al, 2020;Sharmeen et al, 2020;Sormani et al, 2020). Whether this is associated to the preferential depletion of IgM-producing B cells by these treatments (Looney et al, 2008) remains to be shown.…”
Section: Discussionsupporting
confidence: 78%
“…1), suggesting that most MS treatments that largely exhibit limited persistent effects on the innate immune and CD8 T cell responses would have limited influence on COVID‐19. SARS‐CoV‐2 is eliminated by the majority of people with MS and other autoimmunities on immunotherapies, without significant consequences [34–56] (Table 1). Anti‐viral antibodies, notably those targeting the receptor binding domain of the viral spike protein, clearly neutralize the virus [57,58] and can contribute to the elimination of the primary SARS‐CoV‐2 infection in humans [58,59].…”
Section: Introductionmentioning
confidence: 99%